Public diplomacy of the Japan Foundation: A case study of the 2023 online lecture series in Indonesia - Putri, Meisya Maurent Viayu Sasongko; Rosyida, Hamdan Nafiatur; Adzmy, M. Fadzryl (Priviet Social Sciences Journal, 2025)
The Japan Foundation (JF) plays a central role in strengthening the sociocultural foundation of bilateral relations between Indonesia and Japan. To promote mutual understanding, the JF adapted its public diplomacy strategy to an online format when the COVID-19 pandemic posed significant challenges. This study aims to analyze JF's strategy through its 2023 Online Lecture Series on Japanese Culture (OLS) program in Indonesia. Utilizing a descriptive qualitative approach with interviews and a literature review, and applying Mark Leonard's public diplomacy concept, this study examines how the JF implemented its strategy. The findings show that the JF successfully executed three key dimensions of public diplomacy. News Management was conducted through the rapid dissemination of information on social media and a responsive approach to audience interactions. Strategic Communication was embodied by the well-planned OLS program, a proactive initiative designed to cultivate a rich and profound image of Japan, reinforced by a varied selection of themes and a clear connection to the celebration of diplomatic relations. Finally, Relationship Building was strengthened through long-term collaborations with local institutions and the facilitation of dialogue. Despite facing technical and material challenges, OLS proved effective in reaching a wider audience and contributed to maintaining mutual trust. This research also offers a novel perspective on how digital adaptation and online strategies can effectively engage youth and sustain transnational collaboration, making OLS a reference for future hybrid diplomacy in Southeast Asia.